2003
DOI: 10.1046/j.1365-2141.2003.04440.x
|View full text |Cite
|
Sign up to set email alerts
|

Fidelity and reproducibility of antisense RNA amplification for the study of gene expression in human CD34+ haemopoietic stem and progenitor cells

Abstract: Summary. Microarrays provide a powerful tool for the study of haemopoietic stem and progenitor cells (HSC). Because of the low frequency of HSC, it is rarely feasible to obtain enough mRNA for microarray hybridizations, and amplification will be necessary. Antisense RNA (aRNA) amplification is reported to give high-fidelity amplification, but most studies have used only qualitative validation. Before applying aRNA amplification to the study of HSC, we wished to determine its fidelity and reproducibility, and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…In their reports [35], a large amount of supporting online materials and raw data including those for 4289 genes were attached, which were obtained by using Affymetrix systems (the above is excerpted with permission from NB Ivanova et al, Science 298: 601-604 (2002); copyright 2002 AAAS). Similar trials were performed by Park et al [37], Ma et al [38], and Attia et al [39]; however, the data obtained cannot be compared among the reports, because the microarray systems and fractionation methods used were different. Also, overlapping genes were rarely observed because the stem cell compartments sorted out were different.…”
Section: Molecular Signature Of Stemness Of Hematopoietic Stem/progeniessupporting
confidence: 49%
“…In their reports [35], a large amount of supporting online materials and raw data including those for 4289 genes were attached, which were obtained by using Affymetrix systems (the above is excerpted with permission from NB Ivanova et al, Science 298: 601-604 (2002); copyright 2002 AAAS). Similar trials were performed by Park et al [37], Ma et al [38], and Attia et al [39]; however, the data obtained cannot be compared among the reports, because the microarray systems and fractionation methods used were different. Also, overlapping genes were rarely observed because the stem cell compartments sorted out were different.…”
Section: Molecular Signature Of Stemness Of Hematopoietic Stem/progeniessupporting
confidence: 49%
“…Similarly, Scheidl et al (20) and others (10,2123) have shown highly concordant results generated between amplified RNA and total RNA. In contrast, recent work has shown that gene expression profiling using amplified versus nonamplified RNA is not completely preserved and in some instances show poor correlations (15,24,25). Therefore, it is evident that there is a need for further detailed comparisons of data sets obtained from different labeling methodologies on identical platforms.…”
Section: Introductionmentioning
confidence: 79%
“…To specifically identify targets of constitutive signaling, array analyses were performed on non‐induced cells using a restricted gene set microarray composed of gene targets relevant to infection and immunity. This array had over 380 genes represented as exon‐specific PCR products gridded on glass slides with a design based on minimal cross‐hybridization 17 (for a complete V2 gene list, see Materials and methods ). The U51A data were filtered for all genes with signal above mean + 3 SD of non‐homologous (negative) controls, then using a cut‐off of twofold or greater changes in gene expression with p values less than 0.05.…”
Section: Resultsmentioning
confidence: 99%